Efforts to Improve the Welfare of Rural Communities in the Fields of Agriculture, Education, and Socio-Cultural Aspects - Erwin; Enita Dewi Tarigan; Tulus Joseph Herianto Marpaung; Dame Ifa Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2024)
The KKNT-55 program is carried out to form students who are tenacious, tough, independent, hardworking, squat, and have an entrepreneurial spirit. In addition, by holding KKNT student activities it is hoped that they will become more sensitive, empathetic, and concerned about humanity and the environment. This KKNT activity was carried out using observation, counseling, training, and question-and-answer methods. Before being officially released to the field on July 18 2023, the executors first conducted a review and observation of the location. After carrying out the review, the implementer then designs the activities or programs that will be implemented in the previously determined village. In its implementation, the implementers mingle directly with the community and also become laypeople to find out what the problems are in the village. Programs that were successfully implemented in the KKNT-55 activities included: